Academic Supervision Based on Mentoring in Improving Teacher Competence - Netti Netti; Dahrul Aman Harahap; Ramdani Ramdani (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
This study aims to examine the implementation of mentoring-based academic supervision in improving teacher competence at SMPN 2 Tebing, Karimun Regency, Riau Islands Province, Indonesia. The research employed a mixed-methods case study design. In the first phase, a quantitative survey involving 29 teachers was conducted using a four-point Likert-scale questionnaire covering lesson planning, classroom implementation, and learning evaluation. The results show a weighted mean score of 2.94, indicating that teacher competence is in the “Good” category, with the majority of responses at the competent level. However, disparities remain, as a small proportion of teachers demonstrate low performance. In the second phase, qualitative data obtained through written interviews, observations, and document analysis revealed that the effectiveness of supervision was influenced by a collaborative pre-observation dialogue, continuous mentoring, and constructive feedback. These factors reduced teacher anxiety, increased openness, and strengthened motivation for professional growth. The findings confirm that mentoring-based academic supervision contributes significantly to sustainable teacher competence development. Strengthening the instructional leadership role of school principals and institutionalizing mentoring-oriented supervision are therefore recommended to achieve higher levels of professional excellence